Rural living environment predicts social anxiety in transgender and gender nonconforming individuals across Canada and the United States. (August 2019) - Kaplan, Simona C.; Butler, Rachel M.; Devlin, Emily A.; Testa, Rylan J.; Horenstein, Arielle; Swee, Michaela B.; Heimberg, Richard G.
Highlights: Living environment affected social anxiety (SA) among transgender individuals. Rural environments were associated with greater SA than urban environments. Living environments were not associated with degree of social support (SS). Living environment moderated the relationship between SS and SA. SS was more protective against SA in urban and suburban than rural environments. Abstract: Transgender and gender nonconforming (TGNC) individuals frequently confront discrimination, rejection, and violence. Such experiences may put TGNC individuals at risk for minority stress and associated psychiatric symptoms. Protective factors like social support, pride in one's gender identity, or connectedness to similar others may make TGNC individuals less vulnerable to psychiatric symptoms, and the presence of risk and protective factors may vary depending on living environment. This study examined the relationship of living environment (urban vs. suburban vs. small-town/rural) to social anxiety (SA) in a sample of 902 TGNC individuals who participated in the Trans Health Survey. Analysis of variance revealed a significant difference in SA across living environments. Those living in small-town/rural environments reported significantly higher levels of SA compared to those living in urban environments. There was a trend-level difference in SA in suburban compared to urban environments. Linear regression analyses revealed that living environment significantly moderated the relationship between social support and SA. Higher social support was more protective against elevated SA in urban and suburban than in small-town/rural environments. This study is the first to demonstrate the experience of elevated SA among TGNC individuals living in rural environments. Implications and future directions for research are discussed.